Global economy and the euro area: Uncertainty weighs on trade and investment - Claus Michelsen; Dawud Ansari; Guido Baldi; Geraldine Dany-Knedlik; Hella Engerer; Stefan Gebauer; Malte Rieth; Aleksandar Zaklan (DIW Weekly Report, 2018)
The global expansion weakened somewhat in the third quarter while the downside risks have increased. DIW Berlin's forecast- almost unchanged-indicates an expansion in global economic production of 4.3 percent for 2018 and 3.9 percent for 2019. In 2020, momentum will slow down further to 3.6 percent. In some countries, temporary factors contributed to the economic slowdown. In major advanced economies, private consumption remains the mainstay of the economy due to the good labor market situation. However, corporate investment and foreign trade are increasingly suffering from the current major political uncertainties. Brexit and the Italian crisis pose risks to investment and consumption and if the trade dispute escalates, there is also a risk of a global recession. Monetary policy should remain expansionary for the time being. No more significant fiscal policy stimuli are to be expected, especially since government measures in the US will expire in the forecast period.
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook